In the Maelstrom of Political Remembering (KULT_online, 2008)
Using what he describes as an argumentation- and conflict-historical method, historian Christian Lotz explores the problematic of interpreting population displacements and the former eastern territories of the German Reich. For his dissertation, Lotz studied organisations whose actions were pivotal in distributing memory cultures, from the Landsmannschaft Schlesien (an organization of displaced persons from Silesia, the former eastern territory of the German Reich) to the Ministry of State Security. His focus is on the years from 1948-1972, which he separates into three phases of memory politics.